Tax reform, tax shifting and enterprise innovation - Qi, Rang-Kun; Xiong, Zhuang; Bilan, Yuriy (Technological and Economic Development of Economy, 2025)
Fiscal and tax policies, as important forms of government regulation and control of the economy, have a profound impact on both macroeconomics and microeconomics and have been widely studied by scholars. To deeply explore the relationship between tax reform and enterprise innovation, based on classic financial theories such as financing constraints and tax shifting, annual data on Chinese A-share listed companies from 2009 to 2022 and the time-varying difference-in-differences method, we investigated the impact mechanism and economic effects of the “replace the business tax with a value-added tax” policy (VAT reform)on enterprise innovation and examined the moderating effect of the tax shifting ability during this process. The research results indicate the following: VAT reform can lower the tax base of enterprises, reduce cash outflows, and alleviate financing constraints, which helps enterprises stimulate innovation vitality and enhance R&D investments. The negotiation leverage that a company possesses in dealings with its providers and purchasers influences its capacity to transfer fiscal burdens. The enhancement of corporate innovation resulting from the VAT reform is notably pronounced. In contrast to state-owned enterprises, non-state-owned enterprises face fierce market competition and greater survival pressure and do not undertake policy-related activities. They are more sensitive to the tax reduction effect of the VAT reform and are more willing to carry out innovative activities when pursuing long-term development. At the same time, they are also more willing to enhance their tax shifting ability to fully obtain policy dividends for enterprise innovation. This conclusion can help the government correctly judge and comprehensively evaluate the effect of the VAT reform, providing management insights into how the government can better improve tax arrangements and promote enterprise innovation to achieve balanced development and how enterprises can better obtain policy dividends to promote technological innovation.